Pengaruh Bumdes dalam Pengembangan Sistem Aksesibilitas Industri Kreatif, Seni dan Budaya Menuju Desa Wisata Mandiri Berkelanjutan - Muhamad Muhamad; Dicky Sopjan; Sri Rahayu Budiani; Nurul Chamidah; Endah Nurhawaeny Kardiyati (Jurnal Pemberdayaan Umat, 2022)
Purposes: To determine programs that are able to encourage the growth of community initiatives and creativity, especially the development of accessibility systems, development of creative industries, development of arts and culture towards independent and sustainable tourism villages supported by the existence of BUMDes. Research Methodology: The research method carried out with a qualitative descriptive approach is a research method that utilizes qualitative data and is described descriptively. Qualitative descriptive studies and research are used to analyze events, phenomena, or social conditions at the research location. Results: The results of the analysis and discussion can be seen that the program is able to develop existing local potential, both natural resources and human resources, and the program is able to encourage community independence with all the impacts it causes and is able to help empower the community. Limitations: The limited time for the implementation of the service is very short, namely 8 months.. Contributions: determine programs that are able to encourage the growth of community initiatives and creativity, especially the development of accessibility systems, development of creative industries and development of arts and culture towards independent and sustainable tourism.